Binary Image Data Hiding Using Matrix Encoding Technique in Sensors. (18th November 2013) - Huy, Phan Trung; Kim, Cheonshik
Abstract : It is very important to protect the copyright of digital images in wireless transmission, because people often use a smart phone in their daily life. Traditional security schemes are computationally expensive, and they introduce overhead, which shortens the life of the image sensors. In this paper, we present an Improved Matrix Encoding (IME) scheme for hiding data into a two-color binary image. Our proposed scheme improved the CPT scheme. In the CPT scheme, each block F of q = m × n pixel of G is changed by at most two pixels for hiding data. CPT scheme's embedding rate is r = log 2 q + 1 . The IME scheme is shown approximately as a 2 r - 2 embedding rate, while Tseng-Pan's modified CPT scheme (MCPT) is an r - 1 embedding rate. Therefore, IME's embedding rate is higher than that of the MCPT scheme. In our experiment, we demonstrate that our proposed schemes are superior to those of the CPT and MCPT schemes.